2015
DOI: 10.2169/internalmedicine.54.3397
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy and Eosinophilic Pneumonia Coincidentally Induced by Treatment with Daptomycin

Abstract: A 34-year-old man with 22q11.2 deletion syndrome (DiGeorge syndrome) concurrently suffered from myopathy and eosinophilic pneumonia shortly after receiving daptomycin (DAP) for right-sided infective endocarditis. The simultaneous occurrence of these phenomena in relation to DAP therapy has not been previously well described. An allergic reaction was suspected as a possible etiology of these DAP-related complications. This case highlights the need for close observation in order to detect both musculoskeletal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Interest-ingly, 3 cases reported the onset of daptomycin-induced AEP shortly after the third day of exposure but actually all patients had been previously exposed to daptomycin, suggesting a priming immunologic effect. Hagiya et al [95] reported a case of patient who developed AEP after the third day of daptomycin administration. This very short treatment regimen was in fact a re-exposure for the patient, being the primary challenge 20 days earlier [95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest-ingly, 3 cases reported the onset of daptomycin-induced AEP shortly after the third day of exposure but actually all patients had been previously exposed to daptomycin, suggesting a priming immunologic effect. Hagiya et al [95] reported a case of patient who developed AEP after the third day of daptomycin administration. This very short treatment regimen was in fact a re-exposure for the patient, being the primary challenge 20 days earlier [95].…”
Section: Discussionmentioning
confidence: 99%
“…Hagiya et al [95] reported a case of patient who developed AEP after the third day of daptomycin administration. This very short treatment regimen was in fact a re-exposure for the patient, being the primary challenge 20 days earlier [95]. Zimmer et al [105] reported a similar case, in which the patient presented a daptomycin-induced AEP with sudden respiratory distress 9 days after a 3-day re-challenge of daptomycin, 2 weeks after priming.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea was the most common documented symptom associated with eosinophilic pneumonia followed by the presence of either pulmonary infiltrates or opacities on chest x-ray or CT [2] . Both of our patients had dyspnea and pulmonary infiltrates on the CT, but EP patients might present with fever in the absence of respiratory symptoms [5] , [10] , [11] . EP may or may not be associated with peripheral blood eosinophilia, however pulmonary eosinophilic infiltrates or BAL eosinophilia are the corner stone for the diagnosis of EP.…”
Section: Discussionmentioning
confidence: 99%